2017
DOI: 10.1002/adem.201700098
|View full text |Cite
|
Sign up to set email alerts
|

Net Shape 3D Printed NdFeB Permanent Magnet

Abstract: Three dimensional printing enables realization of complex shape rare earth permanent magnet that enable unlocking the full potential of electrical devices for energy consumption and renewable energy production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
94
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(100 citation statements)
references
References 39 publications
4
94
1
1
Order By: Relevance
“…The PBF process can be divided into the heating source. Following commonly used PBF printing techniques are used to investigate the capability to print hard or soft magnets: electron beam melting (EBM) [15], selective laser melting (SLM) [16,17,18,19,20,21], and selective laser sintering (SLS). SLS does not completely melt each powder layer but sinter the particles to retain their original microstructure.…”
Section: Introductionmentioning
confidence: 99%
“…The PBF process can be divided into the heating source. Following commonly used PBF printing techniques are used to investigate the capability to print hard or soft magnets: electron beam melting (EBM) [15], selective laser melting (SLM) [16,17,18,19,20,21], and selective laser sintering (SLS). SLS does not completely melt each powder layer but sinter the particles to retain their original microstructure.…”
Section: Introductionmentioning
confidence: 99%
“…It shows a mean powder size distribution of about 40 μm. The flow rate of 3.33 g s −1 is comparable to other powders typically used for 3D printing . Its chemical composition has significantly less amount of rare earth metals (MQP‐S ≈8 at%) compared to powder usually used for the production of conventional sintered magnets (≈14–18 at%).…”
Section: Amount Of Occurring Phases (ϕ η Nd‐rich Oxides) Grain Simentioning
confidence: 93%
“…The high heating and cooling rates of the laser make the solidification sequence difficult to control . Recently, it has been demonstrated that fine‐tuning the laser parameters may result in stabilization of the intended Fe 14 Nd 2 B phase with reduced (but still present) iron segregation for high cooling rates and the MQP‐S powder used . In general, microstructure and related properties of 3D printed (SLM) components are mainly influenced by processing parameters (laser power, laser scan velocity, laser scan grid space, substrate conditions, thickness of powder layer) and powder characteristics (particle shape, rheology, particle size, inner porosity, purity, humidity) …”
Section: Amount Of Occurring Phases (ϕ η Nd‐rich Oxides) Grain Simentioning
confidence: 99%
See 2 more Smart Citations